ETNOMATEMATIKA PADA BATIK SIDOMUKTI INDRAMAYU DALAM PEMBUKTIAN PHYTAGORAS - Nirmalasari, Dinar; Rofiroh, Rofiroh; Mahuda, Isnaini (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2025)
Batik is a combination of art and technology. Batik has various types and motifs that vary depending on the region. In Indramayu itself there are several types of batik, one of which is batik with the Sidomukti motif. Ethnomathematics is a science that studies the relationship between mathematics and culture. Through this knowledge, various mathematical aspects can be studied that can be found in Sidomukti batik motifs. The aim of this research is to find out the Sidomukti batik motif pattern when linked to the Pythagorean theorem and can be used as an example to convey material proving the Pythagorean Theorem in schools. The research used is qualitative descriptive research with the research object being batik cloth with sidomukti motifs. Mathematically, the sidomukti motif can be approximated by flat rectangular and triangular shapes. From the research, the results showed that there is a mathematical aspect, namely the proof of the Pythagorean Theorem in the Indramayu cultural element, namely the sidomukti batik motif.